Studies on The Chemical Constituents of Bark Roots of Phyllanthus columnaris - A. NASSER, JAMAL; YAACOB, W.A.; B. DIN, LAILY (Asian Journal of Chemistry, 2010)
Fractionation of the ethyl acetate extracts of the bark roots of Phyllanthus columnaris of the Euphorbiaceae family, has led to the isolation and structural elucidation of three different triterpenoids. The separations of the chemical components were carried out by different chromatographic techniques and their structures were elucidated by spectroscopic methods including nuclear magnetic resonance as well as mass spectrometry. Three compounds were isolated and identified; that are lupeol acetate, lupeol and friedelin.